Navigating Governance Dynamics: The Interplay Between Data Governance, Corporate Governance, and Organizational Performance - Addagada, Tejasvi Chandrarkar (Digital Repository of Theses, 2025)
Using a wide range of literature and data sources, this study explores the relationship between data governance, organizational performance, and corporate governance in different organizations. It explores the extent to which the maturity of data governance policies and procedures impacts effectiveness (Sargiotis, 2024). Through bibliometric analysis, the study defined clear boundaries for data governance and also examined previous and ongoing research trends while identifying fifteen factors that contribute to the data governance domain. It also examines if factors of corporate governance moderate the relationship between processes of data governance and organizational outcomes, and then, the extent to which the convergence of corporate and data governance goals contributes to improved performance. To validate these relationships empirically, the study formulates and tests three hypotheses using quantitative research methodologies, focusing on direct influences, moderating effects, and strategic alignment between governance domains. Management and staff from various businesses worldwide having front office or back-office operations in India, were asked to provide responses to questionnaires. To validate conceptual model, statistical methods such as reliability, regression, and correlation analysis were employed. The research highlights whether data governance improves efficiency in operations and which factors like accuracy of data, thereby insights, security, and compliance contribute the most. At the same time, the research indicates how facets of corporate governance including leadership structures, regulatory adherence, risk management and accountability influence the performance of organizations through apt governance of data. One of the findings is higher the maturity in data governance the better is the performance of organization. This can be enabled by improving customer satisfaction, efficiency of daily operations, engagement of employees, time to market as factors enhancing brand value and reputation. Furthermore, the second hypothesis proves that corporate governance acts as a moderating factor in organizations governing data to improve on their efficiency. Specifically, organizations with strong corporate governance frameworks experience benefits from data governance initiatives through improved accountability structures, risk management, and stronger compliance. Adding to the research, the third hypothesis finding reveals that the alignment of objectives among corporate governance and data governance is positively associated with higher performance. The research findings offer important know-how to industry leaders along with policymakers and research experts who should study governance mechanisms. Future research should investigate additional factors such as technological innovations and influences to enhance governance frameworks further.